Evidence for topological defects in a photoinduced phase transition - Zong, Alfred; Fine, Boris V. (Nature physics, 2019)
Three different ultrafast probes investigate a non-adiabatic phase transition and find substantial evidence of topological defects inhibiting the reformation of the equilibrium phase.